Body type and health risk / Sharifah Maimunah Syed Mud Puad - Syed Mud Puad, Sharifah Maimunah (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Body type, also known as somatotype, refers to an individual’s body shape and composition, influenced by the way muscle and fat are distributed throughout the body (Samodra et al., 2023; Kamarudin et al., 2021; Carter, 2002). Certain body types may be associated with increased health risks, but it is important to note that health risks are not solely determined by body type. Instead, a mix of factors, including genetics, lifestyle, diet, physical activity level, and overall fitness, contribute to an individual's health risk profile. Body type has been demonstrated to be related to cardiovascular disease (Parnell, 1959; Carter & Heath, 1990; Williams et al., 2000; Kamarudin et al.,2021). Individuals predominantly exhibiting endomesomorph characteristics have a higher risk of coronary disease (Kamarudin et al., 2023; Williams et al., 2000; Parnell, 1959). Increased body weight with higher fat composition has been linked to higher coronary heart risk factors, which might be mirrored in endomorphy (Carter & Heath, 1990). Abdominal obesity exhibited by endomorph individuals increased the risk of heart disease as fat deposition occurs in the heart area (Kamarudin et al., 2023). In another study done by Urrutia-Garce et al. (2015), findings revealed that individuals with type 2 diabetes exhibited a body type of prominent endomorphic and mesomorphic components.